Increased risk of metabolic bone disease in preterms born to preeclamptic mothers: A case-control study - Bezirganoglu, Handan; Karacaglar, Nazmiye Bengu; Kanmaz Kutman, Gozde (Annals of Medical Research, 2023)
Aim: To evaluate if there is an increased risk of metabolic bone disease associated with preeclampsia. Materials and Methods: Preterm infants <32 weeks in gestation and <1500 gr at birth, who were born in our hospital, followed at least six weeks were enrolled. Metabolic bone disease cases were defined as elevated serum ALP concentration >500 IU/L and serum phosphate levels<4 mg/dl with radiological evidence of osteopenia. The control cases had serum ALP concentration ≤ 500 IU/L and serum phosphate levels >5.6 mg/dl. Maternal factors and clinical variables including postnatal drug use, presence of reduced physical activity, hypotiroidism, feeding intolerance and gastrointestinal patology were reviewed for anaylsis. Results: The final analysis included 126 infants with 46 cases and 80 controls. Logistic regression showed birth weight, feeding intolerance, GIS pathology and preeclampsia were associated with the development of MBD. After the data adjusted for birth weight, preeclampsia showed a association with metabolic bone disease in preterms. Conclusion: Our study identifies preeclampsia as a risk factor for MBD in premature infants. Individualized approach to postnatal nutritional support is warranted for infants born to mothers with severe preeclampsia.